Fold boudins : what is that? - Pamplona, J. (2011)
The hypothesis proposed in this work is related with the genesis and evolution, in HT simple shear zones, of a new conceptual structure designed by fold boudin. The field evidences, achieved in the scope of a methodology to analyze the kinematics of shearband boudins (Pamplona & Rodrigues, 2011), are the basis to show how folds evolute until reach a shearband boudin final state. The critical mass factor (Mc) is the responsible for that mechanism. This parameter, which is now being introduced, is controlled by the hickness (t). The systematic analyses of shearband oudins geometry point to the hypothesis that the development of this structure is precluded by a folding phase, according to the following path evolution in HT shear zones shearband boudins: fold => fold boudin => shearband boudin.